ROLE OF THE YOUTH INFORMATION AND COUNSELING CENTER (PIK-R) IN FORMING ADOLESCENT SELF-CONCEPT THROUGH LUDRUK ART - Shafa Fedha (P3I UMSurabaya, 2024)
Adolescence is one of the most dynamic and complex phases of human development. In this case, the self-concept of adolescents needs to be prepared and developed. One of them is through the Youth Information and Counseling Center (PIK-R). PIK-R Elixir is one of the PIK-Rs located in Kapasari Village, Genteng District, Surabaya City. PIK-R Elixir is not only socialization activities, but in PIK-R Elixir there are several activities, one of which is LAK (Ludruk Arek Kapasari). LAK is an innovation from PIK-R related to how they socialize the issues experienced by adolescents in the form of a role through the art of ludruk. The purpose of this research is to find out how the role of PIK-R in the formation of adolescent self-concept through ludruk art. This study is a qualitative research involving 3 participants. Data were obtained through in-depth interviews. The result of this study is that the existence of ludruk art is one of the media that can support the process of self-concept formation